The Analisis Kinerja dan Akurasi Sensor Thermocouple Tipe K dalam Sistem Pengendalian Suhu Reflow Soldering - Purbo Tri Prakoso; Bustanul Arifin; Suryani ALifah (Lembaga Pengembangan Kinerja Dosen, 2025)
The reflow soldering process is an important stage in the assembly of electronic components that requires high-precision temperature control to ensure the quality of the solder joints. This study aims to evaluate the performance of a K-type thermocouple temperature sensor integrated into the solder reflow control system. Evaluation was carried out through temperature measurements at 20 different points, ranging from 35°C to 220°C, with a focus on reading accuracy and error rate. The results of the experiment showed that the type K thermocouple sensor had an error range between 0.02°C to 0.97°C, with an average error value of 0.54°C. These findings indicate that the sensor is stable and reliable enough to be used in industrial applications that demand temperature precision. The advantages of these sensors lie in their cost efficiency, ease of integration, and responsiveness to temperature changes. Nonetheless, periodic calibration is still necessary to maintain long-term accuracy, especially in dynamic work environments. This research contributes to the development of temperature control systems in the electronic manufacturing process, especially in the selection of the right sensors to support production quality. The conclusion of this study confirms that the K-type thermocouple is a practical and economical solution in reflow soldering systems, with sufficient performance to meet industry standards.